Aryl hydrocarbon receptor: a potential target for natural products in the treatment of inflammatory bowel disease - Ran, Lv; Li, Chunrun; Wang, Peng; Tang, Junmei; Qu, Zhengwu; Hao, Yanwei; Zhang, Yi (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD) is a chronic intestinal inflammatory disease driven by genetic, immune, and environmental factors, and its incidence continues to increase worldwide. The existing therapies often face the limitations of insufficient response, obvious side effects, and high medical burden, so it is urgent to develop safe and effective intervention strategies based on new targets. The aryl hydrocarbon receptor (AHR), a crucial environmental sensor, plays an essential role in preserving intestinal barrier function, modulating immune homeostasis, and facilitating microbiota-host interactions through the integration of ligand-mediated signals. Notably, natural products constitute a major source of AHR ligands and exhibit multiple therapeutic potentials to repair the intestinal barrier, modulate immunity, and remodel the microbiota through targeted activation of AHR. This provides a unique theoretical perspective for developing innovative therapeutic strategies. In this review, we systematically explore the fundamental relationship between AHR and IBD, and introduce the receptor's biological characteristics and regulatory mechanisms in detail. In addition, this article further emphasizes the pharmacological properties and molecular mechanisms of various natural products that target AHR as prospective treatments and evaluates their potential for clinical applications.